2003
DOI: 10.1038/sj.bmt.1703876
|View full text |Cite
|
Sign up to set email alerts
|

Common genomic HLA haplotypes contributing to successful donor search in unrelated hematopoietic transplantation

Abstract: Summary:The aim of the study was to identify the most frequent HLA haplotypes in order to optimize donor searches in unrelated hematopoietic stem cell (HSC) transplantation. Pediatric patients from the north of France who underwent initial HLA typing for donor search in our center were included. Patients and family members were broadly typed for HLA class I and II. Patients were further DNA typed at the sequence level for HLA-A, -B, -Cw, -DRB1, and -DQB1 alleles. In 200 of 207 patients HLA haplotypes were assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…Furthermore, for patients with less frequent HLA gene combinations of haplotype frequencies requesting more donor blood samples for complementary typing at the start of the search seems reasonable in order to decrease the delay in finding an UD. 23 In our cohort the number of patients with one or two FH was substantial (38%); therefore the effect of using HLA haplotypes in UD searches can be very relevant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, for patients with less frequent HLA gene combinations of haplotype frequencies requesting more donor blood samples for complementary typing at the start of the search seems reasonable in order to decrease the delay in finding an UD. 23 In our cohort the number of patients with one or two FH was substantial (38%); therefore the effect of using HLA haplotypes in UD searches can be very relevant.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][18][19][20][21] The presence of FH in patients also affects the probability and speed of identifying a matched UD. [22][23][24][25][26][27][28] It is essential to know the HLA distribution of each population at an allelic level in order to define whether a patient has a high or low probability of finding a matched donor. 27 Our group has previously shown that 30% of Northwest European patients became medically unfit during the search process and therefore did not receive a HSCT (which was unrelated to donor availability).…”
Section: Introductionmentioning
confidence: 99%
“…3,[13][14][15] An alternative must be found for these patients. Should this alternative be unrelated CB or haplo-identical graft?…”
Section: Discussionmentioning
confidence: 99%
“…20 For B18, B27, B44 and B51 serotypes, B-Cw associations in the patient were evaluated with respect to data available in the BMDW registry and with published and local databases. [9][10][11][12][13] For example, a low-probability estimate would be assigned for a patient with the A2-B51-Cw*02-DR8 haplotype, since a very strong linkage with Cw*1402 on this haplotype has been observed (Tiercy J-M, unpublished data). When the two haplotypes of the patient did not belong to the most frequent ones, the search qualified as high when the most common alleles are identified by four-digit typing for each locus based on the frequency distribution described by Hurley et al 21 The BMDW search program, which lists the potential donors that are allele mismatched for each locus, provides useful Table 1 The 10 most frequent haplotypes in Caucasoids based on the phenotypes computed by Boucher et al 19 …”
Section: Probability Assessmentmentioning
confidence: 99%
“…5,9,10 However, high-resolution typing of common ABDR haplotypes disclosed further allelic diversity and multiple bilocus associations (B-C, DR-DQ), thereby increasing the difficulties of the searches. As an example, the A2-B44-DR11 haplotype may comprise any of the three following five-loci combinations: A*0201-B*4402-Cw*0501-DRB1*1101-DQB1*0301, A*0201-B*4402-Cw*0501-DRB1*1104-DQB1*0301 and A*0201-B*4402-Cw*0704-DRB1*1101-DQB1*0301.…”
Section: Introductionmentioning
confidence: 99%